2021
DOI: 10.1530/ec-21-0294
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytomas and paragangliomas in von Hippel–Lindau disease: not a needle in a haystack

Abstract: Objective: Pheochromocytomas are a hallmark feature of von Hippel-Lindau disease (vHL). To our knowledge, this is the first systematic review with meta-analysis evaluating the frequency of pheochromocytomas and/or paragangliomas (PPGL) in patients with vHL, as well as among patients with different vHL subtypes. Design: Systematic review with meta-analysis. Methods: We searched on MEDLINE, Scopus and Web of Science. We included primary studies assessing participants with vHL and reporting on the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 91 publications
(605 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, more men than women were reported to have PPGL due to VHL PVs irrespective of germline or somatic status. The same observation was made in a meta-analysis focused specifically on PPGL patients with VHL disease [ 102 ]. Other studies found that the involved organs in germline VHL -mutated patients are not associated with sex but rather with age and mutation type [ 103-105 ].…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless, more men than women were reported to have PPGL due to VHL PVs irrespective of germline or somatic status. The same observation was made in a meta-analysis focused specifically on PPGL patients with VHL disease [ 102 ]. Other studies found that the involved organs in germline VHL -mutated patients are not associated with sex but rather with age and mutation type [ 103-105 ].…”
Section: Discussionmentioning
confidence: 55%
“…Regarding PPGL, the estimated lifetime risk is 10–25% [ 11 ]. According to a systematic review and meta-analysis of VHL-associated PPGL that included 4263 VHL cases, the pooled frequency of PPGL was 19.4% [ 12 ]. VHL is classified into types 1 and 2; only patients with type 2 VHL develop PPGL.…”
Section: Hereditary Malignancies Associated With Adrenal Tumorsmentioning
confidence: 99%
“…Germline and somatic mutations in major susceptibility genes associated with hypoxia signaling involved in the PCC development, include the tumor suppressors such as VHL1 , the SDH complex (genes encoding the four subunits, A,B,C,D) and occasionally, the egl-9 family hypoxia-inducible factor 1/Prolyl hydroxylase domain 2 protein ( EGLN1/ PHD2) ( 62 , 63 ). Recently, ten new genes have been added to this list and those associated with the hypoxia pathway include HIF-2α (endothelial PAS domain containing protein 1, EPAS1 ) ( 64 , 65 ), FH ( 66 ), and PHD1 (egl nine homolog 2, EGLN2 ) ( 67 ), suggesting that a mutation in any of these major genes involved in the VHL-HIF axis can lead to PCC or PGL development.…”
Section: Hypoxia Inducible Factors: Overview Of Structure Function An...mentioning
confidence: 99%